Adsorption and desorption characteristics of pymetrozine in goji berry soils of China's Qinghai–Tibet Plateau. Issue 2 (3rd March 2020) - Chen, Hongyu; Guo, Liangzhi; Li, Wei; Weng, Hua; Wei, Youhai; Li, Qiurong; Guo, Qingyun
Abstract: The adsorption–desorption processes of pymetrozine were investigated in three cultivated soils in China through a batch method. Pymetrozine was determined by high-performance liquid chromatography (HPLC). At a relatively low temperature, the adsorption of pymetrozine improved with increasing organic matter content, and the Freundlich model precisely illustrates the adsorption isotherms. The adsorption of pymetrozine was classified as physical, considering that the Gibbs free energy change values of this process in the three soils ranged from –21.195 kJ/mol to –23.956 kJ/mol. The Δ H value was –37.236 kJ/mol for soil A, –13.723 kJ/mol for soil B, and –9.154 kJ/mol for soil C, suggesting that the major interaction in the adsorption involved hydrogen bonds and that the adsorption of pymtrozine in the three soils was exothermic. Soil C was shown to have the highest hysteresis among the samples. The hysteresis was enhanced at high temperatures for soil B and soil C but reduced for soil A. Pymetrozine adsorption increased with decreasing temperature, suggesting that pymetrozine may infiltrate groundwater at high temperatures.